المعتقدات الوالدية في التنشئة كما يدركها الأبناء وعلاقتها بالمشكلات الانفعالية لدى طلبة سخنين - أبو يونس، محمد شريف عرنوس; التاج، هيام موسى مصطفى (جامعة عمان العربية - عمادة البحث العلمي والدراسات العليا, 2021)
هدفت الدراسة الحالية للكشف عن المعتقدات الوالدية في التنشئة كما يدركها الأبناء وعلاقتها بالمشكلات الانفعالية لدى طلبة منطقة سخنين. وتكونت عينة الدراسة من (٣٠٠) طالب وطالبة، منهم (161) طالبا، و(139) طالبة من طلبة المرحلة الإعدادية والثانوية في منطقة سخنين للعام الدراسي (٢٠١٨- ٢٠١٩). ولتحقيق أهداف الدراسة أعد الباحثان مقياس المعتقدات الوالدية في التنشئة، ومقياس المشكلات الانفعالية؛ فتم استخدام الصدق الظاهري ومؤشرات صدق البناء، واستخدام معادلة كرونباخ ألفا، وإعادة تطبيق الاختبار (test- retest) للتحقق من ثبات المقياسين، وقد كانت مؤشرات الصدق والثبات مقبولة. أظهرت نتائج هذه الدراسة أن نمط المعتقدات الوالدية السائدة كما يدركها الطلبة في منطقة سخنين هو نمط التقبل الوالدي بدرجة تقييم متوسطة، وأظهرت نتائج الدراسة أيضا أن مستوى المشكلات الانفعالية لدى الطلبة في منطقة سخنين جاء بدرجة متوسطة. وأشارت نتائج الدراسة إلى وجود فروق ذات دلالة إحصائية عند مستوى (α=0.05)) بين المتوسطات الحسابية لتقديرات أفراد عينة الدراسة عن أبعاد مقياس المشكلات الانفعالية تبعا لمتغير الجنس، ولصالح الإناث، وعدم وجود فروق ذات دلالة إحصائية عند مستوى (α=0.05) بين المتوسطات الحسابية لتقديرات أفراد عينة الدراسة عن أبعاد مقياس المشكلات الانفعالية تبعا لمتغير المستوى الدراسي، وهناك علاقة عكسية ذات دلالة إحصائية عند مستوى (α=0.05) بين أبعاد مقياس المشكلات الانفعالية والمقياس ككل ونمط التقبل الوالدي، فكانت جميع قيم معاملات الارتباط سالبة ودالة إحصائياً؛ مما يدل على أن اتباع نمط التقبل الوالدي يقلل من المشكلات الانفعالية، وهناك علاقة طردية ذات دلالة إحصائية عند مستوى (α=0.05) بين أبعاد مقياس المشكلات الانفعالية والمقياس ككل ونمط الرفض الوالدي، فكانت جميع قيم معاملات الارتباط موجبة ودالة إحصائيا؛ مما يدل على أن اتباع نمط الرفض الوالدي تزيد من المشكلات الانفعالية.
This study aimed to reveal Parental Beliefs in socialization as Perceived by Children and Its Relation to Emotional Problems Among Sakhnin Students. The study sample consisted of (300) students, including (161) male students and (139) female students in the academic year 2017- 2018. To achieve the objective of the study, the researcher prepared Parental Beliefs in socialization scale and emotional problems scale. Whereas construct, and discriminative validity indicators were calculated for both scales while Cronbach alpha and test-retest reliability indicators were established. Both validity and reliability were at acceptable levels to achieve the objective of the study. The results of this study showed that the dominant parental beliefs pattern, as perceived by the students in the Sakhnin area, is the parental acceptance pattern with an average rating. The results of the study also showed that the level of emotional problems among students in the Sakhnin area came to an average. The results of the study indicated that there were statistically significant differences at the level (α=0.05) between the dimensions of the emotional problems scale according to the sex variable and for the females, and the absence of significant differences at the level (α=0.05) Between the arithmetic averages of the individuals of the study sample on the dimensions of the emotional problems scale according to the grade variable. There is a statistically significant relationship at the level (α=0.05) between the dimensions of the emotional problems scale and the scale as a whole and the pattern of parental acceptance, where all values of correlation coefficients were negative and statistically significant; indicating that the adoption of the parental acceptance pattern minimizes emotional problems. There is a statistically significant relationship at the level (α=0.05) Parental rejection, where all values of correlation coefficients were positive and statistically significant, indicating that parental rejection was associated with increased emotional problems.
Keywords: التنشئة الاجتماعية -- تربية الأبناء -- الاضطرابات السلوكية -- الرعاية الأسرية -- طلبة سخنين